Stres Akademik berhubungan dengan Kejadian Disminore Primer pada Remaja Putri: Academic Stress related to Primary Dysmenorrhea in Young Women - Siti Fatimah; Sri Mintasih; Ruswanti (Journal of Nursing Education and Practice, 2023)
Introduction: As many as 90% of teenage girls worldwide experience problems during menstruation, 50% of women experience primary dysmenorrhea and 10-20% of them suffer from symptoms that are quite severe. Objectives: To determine the relationship between academic stress and the incidence of primary dysmenorrhea in young women at SMA N 1 Ciemas Sukabumi. Method: The design of this study uses a descriptive correlation with a cross-sectional approach. The samples taken in this study were 55 respondents. The instruments used were the Adolescent Stress Scale (ESSA) and the Menstrual Symptom Questionnaire (MSQ). Result: From the univariate test results, it was found that the distribution of young women experiencing dysmenorrhea (85.5%) and academic stress was in the high category (60.0%). And the results of the bivariate test showed that there was a relationship between academic stress and the incidence of primary dysmenorrhea in young women with a p-value of 0.016. Conclusion: From the results of the research that has been done, it can be concluded that the higher the academic stress, the higher the incidence of primary dysmenorrhea.